THE EFFECT OF PUBLIC FACADE CHARACTERISTICS ON CHANGING PEDESTRIAN BEHAVIORS - Kesici, Neslisah; Erkan, Nilgun Colpan (VILNIUS GEDIMINAS TECH UNIV, 2023)
The facades that define the public open space shape the pedestrian behavior by affecting the visual perception of the pedestrians. In the literature on facade and human interaction, there are pioneering studies in the perspective of environmental perception, but there is a lack and method limitation on the effect of the facade on pedestrian behavior. For this reason, the research aims to evaluate pedestrian behaviors in two areas that are variable in terms of facades, together with video analysis and heat maps. Areas of similar typology in Istanbul's Kadikoy district are compared because of the temporary exterior decoration of the historical candy store in case 1 during the New Year's Eve. According to the research findings, there is a significant difference between the quantity of pedestrians exhibiting stagnant and flowing behaviors and the distribution of these pedestrians in the space. In addition, the subcategories of fluid and static behavior in evening and day conditions also reveal interpretable results regarding the front. The results of the research reveal that the facade features of the public space significantly affect the pedestrian behavior, and therefore this issue should also gain importance in the future of public space design.
Keywords: public space design; building facade; pedestrian behaviors; observation; heat map; environmental perception; Architecture